A National Cancer Database‐based nomogram to predict lymph node metastasis in penile cancer. (22nd January 2019) - Peak, Taylor C.; Russell, Gregory B.; Dutta, Rahul; Rothberg, Michael B.; Chapple, Andrew G.; Hemal, Ashok K.
Abstract : Objective: To evaluate the predictive nature of several clinicopathological variables by developing a nomogram predictive for lymph node‐positive disease using the National Cancer Database cohort of patients with squamous cell carcinoma of the penis. Methods: Stepwise logistic regression was used to find the best‐fit model; remaining clinical variables were used to create a nomogram to predict the probability of lymph node‐positive disease. Results: On multivariate analysis, high pathological grade (3–4 vs 1: odds ratio [OR] 3.27, 95% confidence interval [CI] 1.70–6.29; 2 vs 1: OR 2.58, 95% CI 1.39–4.79 [ P = 0.002]), lymphovascular invasion (OR 2.49, 95% CI 1.61–3.84 [ P < 0.001]), and positive clinical lymph node status (N1 vs N0: OR 20.0, 95% CI 11.4–35.7; N2 vs N0: OR 27.8, 95% CI 14.1–55.6; N3 vs N0: OR 49.2, 95% CI 14.8–162.8 [ P < 0.001]) were predictors of lymph node metastasis in penile cancer. The bootstrap‐corrected concordance index of this nomogram was 0.880. Conclusion: Using tumour grade, tumour lymphovascular invasion and clinical lymph node status, we developed a nomogram highly predictive of pathologial lymph node metastasis that, after further external validation, could be helpful in the surgical decision‐making process.